2018
DOI: 10.1038/s41467-018-04033-x
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of mitochondrial dynamics proteins are a targetable feature of human tumors

Abstract: Altered mitochondrial dynamics can broadly impact tumor cell physiology. Using genetic and pharmacological profiling of cancer cell lines and human tumors, we here establish that perturbations to the mitochondrial dynamics network also result in specific therapeutic vulnerabilities. In particular, through distinct mechanisms, tumors with increased mitochondrial fragmentation or connectivity are hypersensitive to SMAC mimetics, a class of compounds that induce apoptosis through inhibition of IAPs and for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 49 publications
4
75
0
Order By: Relevance
“…It has been established that the alteration of mitochondrial dynamics impact tumor development broadly. Alterations to the mitochondrial dynamic network also result in specific therapeutic susceptibilities, in particular, tumors with increased mitochondrial fragmentation or connectivity are hypersensitive to SMAC mimetics and induce apoptosis by blocking the action of inhibitor of apoptosis proteins (IAPs) (124). On the other hand, it was demonstrated that Drp1 expression was strongly increased in distant metastasis of hepatocellular carcinoma (HCC) compared to primary tumors.…”
Section: Mtorc1 and Mitochondrial Dynamic In Cancermentioning
confidence: 99%
“…It has been established that the alteration of mitochondrial dynamics impact tumor development broadly. Alterations to the mitochondrial dynamic network also result in specific therapeutic susceptibilities, in particular, tumors with increased mitochondrial fragmentation or connectivity are hypersensitive to SMAC mimetics and induce apoptosis by blocking the action of inhibitor of apoptosis proteins (IAPs) (124). On the other hand, it was demonstrated that Drp1 expression was strongly increased in distant metastasis of hepatocellular carcinoma (HCC) compared to primary tumors.…”
Section: Mtorc1 and Mitochondrial Dynamic In Cancermentioning
confidence: 99%
“…Moreover, Ang II is a potent mediator of oxidative stress and oxidant signaling leading to vascular premature senescence (Andrés, 2014). In this study, we showed that short-term exposure (1 day Mitochondria exist in a dynamic equilibrium between fragmented and fused states, and mitochondrial dynamics is controlled by fission and fusion (Anderson et al, 2018;Shi et al, 2018). Increased mitochondrial fission and/or attenuated fusion lead to mitochondrial fragmentation and disrupt cellular physiological function (Caja et al, 2017).…”
Section: Discussionmentioning
confidence: 79%
“…Mitochondria play important roles in regulating critical cellular, physiological, and pathophysiological processes (Tezze et al, 2017;Anderson et al, 2018). Alterations in mitochondrial dynamics, which is regulated mainly by the processes of fission and fusion, are implicated in various human diseases including cancer and neurologic and cardiovascular diseases (Anderson et al, 2018;Abuarab et al, 2017;Vásquez-Trincado et al, 2016). Previous studies have demonstrated that dysregulation of mitochondrial dynamics is a key feature of aging (Anderson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of mitochondrial dynamics is essential for development (Chen et al, 2003; Ishihara et al, 2009; Waterham et al, 2007) and dysregulation of its machinery is implicated in a wide range of human diseases, including neuropathies, type II diabetes, and cancer (Anderson et al, 2018; Ranieri et al, 2013; Rovira-Llopis et al, 2017). However, the role of mitochondrial dynamics in other contexts, such as epithelial repair is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%